The ocular surface microenvironment and its regulatory mechanisms - WANG Jinghui; TANG Yan; ZHANG Yongxin; YE Lin (Yanke Xuebao)
The ocular surface is a complex and sensitive system composed of includes various structures including the cornea, tear film and conjunctiva. As the part of the eye directly exposed to the external environment, the ocular surface not only protects the eye, but also plays a vital role in vision. The balance of the ocular surface(OSM) is essential for eye health, and any disruption can lead to ocular surface diseases, such as dry eye and keratitis. With the evolving lifestyle of the modern population, the incidence of Visual Display Terminal (VDT) syndrome has significantly increased, disturbing the OSM balance and leading to a rise in ocular surface diseases, particularly dry eye disease, which severely impacts patients' quality of life. Therefore, it is crucial to conduct comprehensive research into the regulatory mechanisms that maintain OSM homeostasis and explore effective therapeutic strategies. Recent studies have moved beyond traditional anatomical frameworks, uncovering the multi-system coordinated regulatory mechanisms of OSM, providing new insights into maintaining ocular surface homeostasis. The interplay between the nervous, lymphatic, and immune systems not only helps identify key molecules and signaling pathways involved in ocular surface diseases but also offers new opportunities for discovering novel biomarkers and potential therapeutic targets. This article presents a systematic review of the latest advancements in OSM regulatory mechanisms, focusing on the roles of nervous, lymphatic, and immune regulation in maintaining OSM homeostasis and analyzing the interactions among these systems, with the goal of offering new insights for the prevention and treatment of ocular surface diseases.